Gender, Politics and Development in Zimbabwe: Reflections since CEDAW - Zikhali, Whitehead (Advances in Social Sciences Research Journal, 2018)
Although the Convention on the Elimination of all forms of Discrimination Against Women (CEDAW) was instituted about three decades ago, the quest for equality of genders persists across the globe. The disparities prevail across various spheres of life and at different levels of the socio-economic and political strata. The irony is that such conditions prevail in a time where political consciousness and rhetoric are heightened. The explanation lies in structural impediments which continue to be snags on progress particularly in societies rooted in patriarchal cultures. In addition, character misrepresentations and sexualisation of female political figures persist. This paper presents an elaborate survey of the progress made in Zimbabwe since CEDAW and the Beijing Declaration. It draws from an extensive review of existing published research to summarize what has been studied and is currently known about the status of women in politics and the influence of gender on their experiences as participants within the realm of formal politics. The paper recommends increased emphasis on such policies as quota systems and affirmative action in favour of women’s representation.